1994
DOI: 10.1007/bf00711591
|View full text |Cite
|
Sign up to set email alerts
|

Effect of betaine onS‐adenosylmethionine levels in the cerebrospinal fluid in a patient with methylenetetrahydrofolate reductase deficiency and peripheral neuropathy

Abstract: A 16-year-old Japanese girl with 5,10-methylenetetrahydrofolate reductase deficiency showed peripheral neuropathy. There were no significant responses to vitamin B6, vitamin B12 or folate, given alone or in combination. With the addition of betaine monohydrate, she has been free from gait disturbance and muscle weakness. The concentration of S-adenosylmethionine in cerebrospinal fluid, which was undetectable before receiving betaine monohydrate, increased to about the normal level 24 months after treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Also all three patients had other electrophysiological evidence of generalised peripheral nerve involvement. As was seen in patients 1 and 2 here, worsening lower limb neuropathy can herald potential respiratory decompensation (Nishimura et al 1985;Kishi et al 1994). The response of this peripheral neuropathy is often at best limited (Chaabene-Masmoudi et al 2009;Schiff et al 2011); however, in this case series complete electrophysiological resolution was documented in the infantile onset MTHFR case accompanied by normalisation of clinical symptomology, while apparent clinical resolution was seen in patients 1 and 2.…”
Section: Discussionsupporting
confidence: 51%
“…Also all three patients had other electrophysiological evidence of generalised peripheral nerve involvement. As was seen in patients 1 and 2 here, worsening lower limb neuropathy can herald potential respiratory decompensation (Nishimura et al 1985;Kishi et al 1994). The response of this peripheral neuropathy is often at best limited (Chaabene-Masmoudi et al 2009;Schiff et al 2011); however, in this case series complete electrophysiological resolution was documented in the infantile onset MTHFR case accompanied by normalisation of clinical symptomology, while apparent clinical resolution was seen in patients 1 and 2.…”
Section: Discussionsupporting
confidence: 51%
“…Thus, it is a nutrient that plays an important role in the health of the cardiovascular system. Studies have suggested that betaine helps to reduce potentially toxic levels of homocysteine, a naturally occurring amino acid that can be harmful to blood vessels, thereby contributing to the development of heart disease, stroke, and Alzheimer's disease (2)(3)(4). In addition, betaine has been shown to enhance the expression and activity of key participants in vascular inflammation related to deteriorated vessel function, such as hyperosmotic cell shrinkage or hypoosmotic cell swelling in liver and kidney (5,6).…”
mentioning
confidence: 99%
“…Pooled data from many studies showed that mild homocysteinemia occurs in 9-42% of subjects below 50 years of age who have peripheral or cerebral occlusive arterial disease, myocardial infarction, or thromboembolism [23]. About 21% of young patients with coronary artery disease, 24% of patients with cerebrovascular disease, and 32% of patients with peripheral vascular disease are found to have mild postmethionine homocysteinemia.…”
Section: Mild Homocysteinemiamentioning
confidence: 99%